IL-17+ CD8+ T cell suppression by dimethyl fumarate associates with clinical response in multiple sclerosis - Lückel, Christina; Picard, Felix; Raifer, Hartmann; Campos Carrascosa, Lucia; Guralnik, Anna; Zhang, Yajuan; Klein, Matthias; Bittner, Stefan; Steffen, Falk; Moos, Sonja; Marini, Federico; Gloury, Renee; et al. (Nature Communications, 2019)
IL-17-producing CD8+ (Tc17) cells are enriched in active lesions of patients with multiple sclerosis (MS), suggesting a role in the pathogenesis of autoimmunity. Here we show that amelioration of MS by dimethyl fumarate (DMF), a mechanistically elusive drug, associates with suppression of Tc17 cells. DMF treatment results in reduced frequency of Tc17, contrary to Th17 cells, and in a decreased ratio of the regulators RORC-to-TBX21, along with a shift towards cytotoxic T lymphocyte gene expression signature in CD8+ T cells from MS patients. Mechanistically, DMF potentiates the PI3K-AKT-FOXO1-T-BET pathway, thereby limiting IL-17 and RORγt expression as well as STAT5-signaling in a glutathione-dependent manner. This results in chromatin remodeling at the Il17 locus. Consequently, T-BET-deficiency in mice or inhibition of PI3K-AKT, STAT5 or reactive oxygen species prevents DMF-mediated Tc17 suppression. Overall, our data disclose a DMF-AKT-T-BET driven immune modulation and suggest putative therapy targets in MS and beyond., Dimethyl fumarate (DMF) is a therapy for multiple sclerosis (MS) with undetermined mechanism of action. Here the authors find that clinical response to DMF associates with decrease in IL-17-producing CD8+ T cells (Tc17), delineate molecular pathways involved, and show that DMF suppresses Tc17 pathogenicity in a mouse model of MS.